Doing a Dam Better: The Lao People’s Democratic Republic and the Story of Nam Theun 2 - Thanju, Jeewan Prasad (Hydro Nepal: Journal of Water, Energy and Environment, 2012)
By Ian C. Poster and Jayasankar Shivakumar, Editors Washington, DC: The International Bank for Reconstruction and Development/World Bank, 189pp., US$25.00. DOI: http://dx.doi.org/10.3126/hn.v9i0.7077 Hydro Nepal Vol.9 July 2011 69-70